Increasing the perceived malleability of gender bias using a modified Video Intervention for Diversity in STEM (VIDS). (August 2018) - Hennes, Erin P.; Pietri, Evava S.; Moss-Racusin, Corinne A.; Mason, Katherine A.; Dovidio, John F.; Brescoll, Victoria L.; H. Bailey, April; Handelsman, Jo
Scholars are increasingly responding to calls for interventions to address persistent gender disparities in the sciences. Yet, interventions that emphasize the pervasiveness of bias may inadvertently damage efficacy to confront sexism by creating the perception that bias is immutable. We examined this possibility in the context of a successful bias literacy program, Video Interventions for Diversity in STEM (VIDS; Moss-Racusin et al., in press). In two studies with working adults from the general public ( N = 343) and science faculty ( N = 149), we modified VIDS by developing a module (UNITE) that offers tools for addressing bias and promotes the mindset that bias is malleable. VIDS alone was sufficient to increase awareness of bias, reduce sexism, and improve bias identification. However, UNITE buffered against perceptions that bias is immutable and restored self-efficacy to address bias. We conclude that interventions must aim not only to increase bias literacy but also offer concrete tools and avoid implying that these problems are insurmountable.